Centella asiatica : alternative dry skin therapy in type 2 diabetes mellitus - Lili Legiawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Diabetes mellitus (DM) in Indonesia has rapidly increased during recent years. World Health Organization (WHO) predicted that in 2030, Indonesia would be ranked fourth for the largest DM patients in the world. As the disease progresses, uncontrolled type 2 DM (T2DM) results in dry skin as the most prevalent skin disorder. Despite the prevalence and morbidities that lead to infection, ulcer, gangrene that can lead to amputation when insufficiently treated, dry skin in T2DM has limited therapeutic options. Currently, available therapies for dry skin in T2DM have not considered factors of hyperglycemia and hyperinsulinemia, which disturb skin homeostasis. Nonetheless, in T2DM, there are neuropathy and biostructural changes of the skin which induce dry skin. Alternative herbal medicine, Centella asiatica is getting well-known nowadays because of its vast amount of benefits. Centella asiatica has been studied for its antioxidant, antidiabetic, anti-inflammation, antiglycation, and neuroprotective activities. Furtherly, these properties may display benefits when introduced to T2DM dry skin therapy. The previous clinical study had shown that topical C. asiatica improved dry skin. This clinical study was also supported by in vitro studies. Currently, pharmacological profile studies of C. asiatica including dosage, toxicity, and safety have been available. This article aimed to review the current literature on the potential of C. asiatica as an alternative to treat dry skin in T2DM.